Increase in Suicidal Thinking During COVID-19. (May 2021) - Fortgang, Rebecca G.; Wang, Shirley B.; Millner, Alexander J.; Reid-Russell, Azure; Beukenhorst, Anna L.; Kleiman, Evan M.; Bentley, Kate H.; Zuromski, Kelly L.; Al-Suwaidi, Maha; Bird, Suzanne A.; Buonopane, Ralph; DeMarco, Dylan; et al.
There is concern that the COVID-19 pandemic may cause increased risk of suicide. In the current study, we tested whether suicidal thinking has increased during the COVID-19 pandemic and whether such thinking was predicted by increased feelings of social isolation. In a sample of 55 individuals recently hospitalized for suicidal thinking or behaviors and participating in a 6-month intensive longitudinal smartphone monitoring study, we examined suicidal thinking and isolation before and after the COVID-19 pandemic was declared a national emergency in the United States. We found that suicidal thinking increased significantly among adults (odds ratio [ OR ] = 4.01, 95% confidence interval [CI] = [3.28, 4.90], p < .001) but not adolescents ( OR = 0.84, 95% CI = [0.69, 1.01], p = .07) during the onset of the COVID-19 pandemic. Increased feelings of isolation predicted suicidal thinking during the pandemic phase. Given the importance of social distancing policies, these findings support the need for digital outreach and treatment.